A systematic review of the quality, content, and context of breakfast consumption - Mullan, Barbara; Singh, M. (Emerald Group Publishing, 2010)
Purpose – Consumption of breakfast is often associated with important health-related behaviours. For example, skipping breakfast is related to obesity and eating breakfast is also correlated to cognitive, behavioural, and affective components. The purpose of this paper is to review the breakfast eating literature, and investigate the circumstances under which people consume breakfast, what is actually being consumed, and how much breakfast is eaten therefore. Design/methodology/approach – This systematic review summarises the results from 24 studies which focus on who is eating what, where, and with whom. Findings – All 24 of the included studies are of a self-report nature, from which nine were analysed from second-hand survey data. Sample sizes vary from 100 to a total of 35,119 with a reported participants’ age range from two years old to 70 years of age. Ready-to-eat cereal and dairy foods are the most commonly consumed breakfast items across the studies. Between 1.7 and 30 per cent of participants are found to skip breakfast and approximately one-quarter of the studies report that those with lower socio-economic status, non-whites, and females were the groups more likely to omit breakfast. Research limitations/implications – The evidence provided in this review suggests that there is still considerable variation in studies into breakfast consumption. This has implications for future research into breakfast eating if interventions are based on these studies. Originality/value – There are very few systematic reviews detailing the quality, context, and content of breakfast consumption and the lack of consistency in the results show the need for further research to be conducted to find a degree of consistency in how breakfast should be defined and measured.